Landau–Zener transitions and Rabi oscillations in a Cooper-pair box: beyond two-level models - Parafilo, A.V.; Kiselev, M.N. (Физика низких температур, 2018)
We investigate quantum interference effects in a superconducting Cooper-pair box by taking into account the possibility of tunneling processes involving one and two Cooper pairs. The quantum dynamics is analyzed in a framework of three-level model. We compute Landau–Zener probabilities for a linear sweep of the gate charge and investigate Rabi oscillations in a periodically driven three-level system under in- and off-resonance conditions. It was shown that the Landau–Zener probabilities reveal two different patterns: “step”- and “beats”-like behaviors associated with the quantum interference effects. Control on these two regimes is provided by change of the ratio between two characteristic time scales of the problem. We demonstrate through the analysis of a periodically driven three-level system, that if a direct transition between certain pairs of levels is allowed and finetuned to a resonance, the problem is mapped to the two-level Rabi model. If the transition between pair of levels is forbidden, the off-resonance Rabi oscillations involving second order in tunneling processes are predicted. This effect can be observed by measuring a population difference slowly varying in time between the states of the Cooper-pair box characterized by the same parity Вивчено квантові інтерференційні ефекти в надпровідному транзисторі з урахуванням можливості тунелювання однієї або двох куперівських пар. Квантову динаміку системи проаналізовано в рамках трирівневої моделі. Розраховано ймовірності Ландау–Зинера в разі лінійної за часом зміни заряду на затворі, а також досліджено осциляції Рабі в трирівневій системи з періодичним накачуванням в умовах резонансу й поза резонансу. Показано, що ймовірності Ландау– Зинера можуть бути розглянуті в двох режимах, що характеризуються ступінчасто- та биттяподібною поведінкою ймовірності. Перехід між режимами здійснюється за допомогою контролю відношення між двома характерними часами в задачі. Продемонстровано, що в трирівневій системи з періодичним накачуванням за умови, коли прямі переходи між певними парами рівнів дозволено, проблема може бути зведена до дворівневої моделі Рабі. У разі, коли прямі переходи між парами рівнів заборонено, передбачено нерезонансні осциляції Рабі, які включають процеси тунелювання другого порядку. Передбачений ефект може бути виявлений за допомогою вимірювання відносної заселеності станів транзистора з тією ж парністю. Изучены квантовые интерференционные эффекты в сверхпроводящем транзисторе с учетом возможности туннелирования одной или двух куперовских пар. Квантовая динамика системы проанализирована в рамках трехуровневой модели. Рассчитаны вероятности Ландау–Зинера в случае линейного по времени изменения заряда на затворе, а также исследованы осцилляции Раби в трехуровневой системе с периодической накачкой в условиях резонанса и вне резонанса. Показано, что вероятности Ландау–Зинера могут быть рассмотрены в двух режимах, характеризуемых ступенчатои биениеподобным поведением вероятности. Переход между режимами осуществляется с помощью контроля отношения между двумя характерными временами в задаче. Продемонстрировано, что в трехуровневой системе с периодической накачкой при условии, когда прямые переходы между определенными парами уровней разрешены, проблема может быть сведена к двухуровневой модели Раби. В случае, когда прямые переходы между парами уровней запрещены, предсказаны нерезонансные осцилляции Раби, которые включают процессы туннелирования второго порядка. Предсказанный эффект может быть обнаружен с помощью измерения относительной заселенности состояний транзистора с той же четностью.